2017
DOI: 10.3329/bjmb.v8i2.33280
|View full text |Cite
|
Sign up to set email alerts
|

Association of 25-OH Cholecalciferol with Acute Myocardial Infarction

Abstract: Cholesterol and LDL-Cholesterol were found significantly higher in AMI compared to those among healthy controls. Among all study subjects, statistically significant positive correlation of 25(OH)D 3 was found with HDL-C (p=0.014). Significant negative correlation was found with serum TC (p=0.001) and LDL-C (p <0.001). Serum TG was found negatively correlated with 25-hydroxycholecalciferol but it was not statitiscaly significant (p=0.068). In our study Vitamin-D deficiency was found to be significantly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In that studyvitamin D was found to be significantly reduced in AMI patients when compared with that of controls which were 28.50±16.68 ng/ml in cases and 38.32±16.47 ng/ml in controls, P=0.011. 20 In an Indian study, Karur and colleagues included AMI patient from all ages and found 83.5% vitamin D deficiency or insufficiency . 21 In our study we found that all (100%) patients of young (≤40 years) AMI patients had either insufficient vitamin-D level (13.3%) or moderate/ severely deficient vitamin-D level (86.7%).…”
Section: Association Of Serum Vitamin D With Acute Myocardial Infarctmentioning
confidence: 99%
“…In that studyvitamin D was found to be significantly reduced in AMI patients when compared with that of controls which were 28.50±16.68 ng/ml in cases and 38.32±16.47 ng/ml in controls, P=0.011. 20 In an Indian study, Karur and colleagues included AMI patient from all ages and found 83.5% vitamin D deficiency or insufficiency . 21 In our study we found that all (100%) patients of young (≤40 years) AMI patients had either insufficient vitamin-D level (13.3%) or moderate/ severely deficient vitamin-D level (86.7%).…”
Section: Association Of Serum Vitamin D With Acute Myocardial Infarctmentioning
confidence: 99%